2018
DOI: 10.1007/s13197-018-3302-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of enzymatic hydrolysis of copra meal: compositions and properties of the hydrolysate

Abstract: This study demonstrated that oligosaccharides from copra meal could be prepared by using a commercial enzyme preparation containing mannanase for use as a prebiotic. The conditions giving the highest hydrolysis rate of the copra meal by the enzyme were pH 4 and temperature of 40 °C with an enzyme to substrate ratio (E/S) of 1092.69 β-mannanase activity unit/g of the dried copra meal. Monosaccharide was the predominant product of the hydrolysis reaction followed by di- and tri-saccharide. Activated carbon treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…It may be due to their content being lower than the limit of detection. This was also in agreement with the work of Thongsook & Chaijamrus (2018) that when using the commercial enzyme Actipro SF‐R™ to hydrolyse defatted copra meal, only oligosaccharides with DP2 and DP3 were detected. As reported previously, β‐mannanase from Aspergillus niger (Ademark et al ., 1998), Aspergillus oryzae (Jana & Kango, 2020) and Trichoderma reesei (Stålbrand et al ., 1993) produces mainly short chain oligosaccharides with low amounts of oligosaccharides with high DP.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It may be due to their content being lower than the limit of detection. This was also in agreement with the work of Thongsook & Chaijamrus (2018) that when using the commercial enzyme Actipro SF‐R™ to hydrolyse defatted copra meal, only oligosaccharides with DP2 and DP3 were detected. As reported previously, β‐mannanase from Aspergillus niger (Ademark et al ., 1998), Aspergillus oryzae (Jana & Kango, 2020) and Trichoderma reesei (Stålbrand et al ., 1993) produces mainly short chain oligosaccharides with low amounts of oligosaccharides with high DP.…”
Section: Resultssupporting
confidence: 92%
“…It has been known that commercial enzymes are relatively inexpensive and are widely applicable on an industrial scale. Thongsook & Chaijamrus (2018) also investigated the production of MOS from copra meal using β‐mannanase present in Actipro SF‐R™, a commercial enzyme preparation derived from Aspergillus niger . The hydrolysate of 3.2% (w/v) defatted and deproteinised copra meal contained monosaccharides as the major product, followed by di‐ and tri‐saccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Use of various substrates such as wheat bran, rice bran and other agricultural waste residues have been reported for the production of xylanase/s [14,37] among which wheat bran is most widely used [18,22,32]. Because of the higher content of mannan in it copra meal is a known substrate for the production of manannases [38,39,40]. After initial optimization by OVAT 2.27 and 20.5 fold yield increase was achieved for xylanase and manannase respectively with incubation time 120h, temperature 37 C, moisture ratio 1:2, inoculums size 1.0% (Table 1).…”
Section: Optimization Of Physicochemical Factors By One Variable At a Time (Ovat) Methodsmentioning
confidence: 99%
“…For instance, there is an increasing trend in the use of oil cakes to produce substrates that will serve as carbon and nitrogen source in manufacturing biochemicals, including enzymes and antibiotics, through fermentation [ 71 ]. Aside from the extensive studies being conducted to optimize the use of copra meal as an alternative feed ingredient, various researchers are now seeking to explore the utilization of copra mannan for the production of prebiotic manno-oligosaccharides (MOS) for food and feed applications [ 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Humans, similar to animals, cannot readily digest copra meal due to its high mannan content.…”
Section: Opportunities and Value-added Applicationsmentioning
confidence: 99%
“…The consumption of CMH was found to improve bowel movements and provide relief from bloating symptoms [ 76 ]. Furthermore, studies have shown that CMH promotes the growth of beneficial microbes in the human intestinal microflora, while reducing the levels of pathogenic bacteria such as Escherichia coli [ 75 , 76 , 77 , 78 ]. Moreover, MOS can be potentially used to replace antibiotic growth promoters and as a mycotoxin and cholesterol binder in poultry diets [ 74 ].…”
Section: Opportunities and Value-added Applicationsmentioning
confidence: 99%